The Carbon Footprint of Surgical Operations: A Systematic Review. Issue 6 (December 2020) - Rizan, Chantelle; Steinbach, Ingeborg; Nicholson, Rosamond; Lillywhite, Rob; Reed, Malcolm; Bhutta, Mahmood F.
Abstract : Summary of background data and objectives: Operating theatres are typically the most resource-intensive area of a hospital, 3–6 times more energy-intensive than the rest of the hospital and a major contributor of waste. The primary objective of this systematic review was to evaluate existing literature calculating the carbon footprint of surgical operations, determining opportunities for improving the environmental impact of surgery. Methods: A systematic review was conducted in accordance with PRISMA guidelines. The Cochrane Database, Embase, Ovid MEDLINE, and PubMed were searched and inclusion criteria applied. The study endpoints were extracted and compared, with the risk of bias determined. Results: A total of 4604 records were identified, and 8 were eligible for inclusion. This review found that the carbon footprint of a single operation ranged 6–814 kg carbon dioxide equivalents. The studies found that major carbon hotspots within the examined operating theatres were electricity use, and procurement of consumables. It was possible to reduce the carbon footprint of surgery through improving energy-efficiency of theatres, using reusable or reprocessed surgical devices and streamlining processes. There were significant methodological limitations within included studies. Conclusions: Future research should focus on optimizing the carbon footprint of operating theatres through streamlining operations, expanding assessments to other surgical contexts, and determining ways to reduce the footprint through targeting carbon hotspots. Abstract : Supplemental Digital Content is available in the text